2021
DOI: 10.30587/ijmt.v1i1.3419
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Paritas Dengan Berat Badan Lahir Rendah (BBLR)

Abstract: One of the indicators that determine a country's health status is the high and low number of the Infant Mortality Rate (IMR). Meanwhile, the incidence of Low Birth Weight (LBW) is one of the main determining factors that contribute to the Infant Mortality Rate (IMR). Many factors cause an increase in the number of IMR, one of which is parity. This study aims to determine the relationship between parity and low birth weight (LBW) in Cendrawasih Dobo Hospital, Aru Islands Regency.This study uses analytical resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The previous argument is supported by Sari & Hasmita (2019), which obtained a p-value = 0.000, meaning there is a parity relationship with the incidence of LBW at Puri Husada Tembilahan Regional Hospital. Fatmawati & Wati (2021), found that a value of p = 0.000, which means there is a relationship between parity number and LBW. Kurniasari (2018), stated that there was a significant relationship between parity and the incidence of LBW at RSIA Annisa Jambi City in 2017 with a p-value of 0.01.…”
Section: Relationship Between Parity and Low Birth Weight At Pku Muha...mentioning
confidence: 98%
“…The previous argument is supported by Sari & Hasmita (2019), which obtained a p-value = 0.000, meaning there is a parity relationship with the incidence of LBW at Puri Husada Tembilahan Regional Hospital. Fatmawati & Wati (2021), found that a value of p = 0.000, which means there is a relationship between parity number and LBW. Kurniasari (2018), stated that there was a significant relationship between parity and the incidence of LBW at RSIA Annisa Jambi City in 2017 with a p-value of 0.01.…”
Section: Relationship Between Parity and Low Birth Weight At Pku Muha...mentioning
confidence: 98%
“…Penyebab utama diantaranya prematuritas, infeksi, asfiksia, hipotermia, dan pemberian ASI tidak adekuat (Pantiawati, 2010). Pencegahan dapat dilakukan melalui peningkatan kualitas kesehatan dalam keluarga.…”
Section: Pendahuluanunclassified